2013
DOI: 10.1159/000354290
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Coronary Stenting in Patients with Variant Angina Refractory to Medical Treatment: A Consecutive Single-Center Analysis

Abstract: Objective: To investigate the efficacy of coronary stenting in patients with variant angina refractory to medical treatment. Subjects and Methods: Variant angina was diagnosed in 81 patients admitted to the Department of Cardiology between January 2003 and June 2011. However, coronary stenting was performed in 21 patients refractory to medical treatment, but coronary angiography and intravascular ultrasound were performed in all patients, and acetylcholine provocative test was performed in 11 of the 21 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…In accordance with the current case, other studies also reported plaque erosion at the site of coronary spasm, which indicates that intracoronary imaging can help to diagnose more complex cases at which standard coronary angiogram does not identify the possible problem or culprit [911]. And stent placement under the guidance of intracoronary imaging represents an attractive therapeutic option in patients with vasospastic angina refractory to aggressive medical therapy [12, 13].…”
Section: Discussionsupporting
confidence: 85%
“…In accordance with the current case, other studies also reported plaque erosion at the site of coronary spasm, which indicates that intracoronary imaging can help to diagnose more complex cases at which standard coronary angiogram does not identify the possible problem or culprit [911]. And stent placement under the guidance of intracoronary imaging represents an attractive therapeutic option in patients with vasospastic angina refractory to aggressive medical therapy [12, 13].…”
Section: Discussionsupporting
confidence: 85%
“…This was impossible for our patient case, who had multi-vessel vasospasms. Patients that are refractory to pharmacologic and percutaneous invasive therapy present most likely a severe vasomotor disorder and need more intensive long medical treatments and continued surveillance [10][11][12]. In some cases, despite good outcomes under medical treatment, 6.1% of patients suffer from ventricular arrhythmia events in the long outcome which requires implantable cardioverter-defibrillator (ICD) use as a considerable tool to improve the long-term prognosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…While this is not standard treatment at the moment, it is a known option with some promising evidence already available. In a single-center analysis in China including 21 patients who underwent coronary stenting in the setting of refractory variant angina, only 1 patient continued to have recurrent episodes of variant angina with 5 patients experiencing occasional chest pain and the remaining 15 patients being asymptomatic [ 21 ]. The authors concluded that with additional supporting evidence, this could become a viable option for this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%